Efficacy of acupuncture in animal models of vascular dementia: A systematic review and network meta-analysis - Li, Guangyao; Shi, Yuling; Zhang, Lu; Yang, Chuanghui; Wan, Ting; Lv, Hang; Jian, Wenxuan; Li, Jinghu; Li, Min (Frontiers in Aging Neuroscience, 2022)
BACKGROUND AND PURPOSE: Acupuncture is widely used in clinical practice for the treatment of vascular diseases. However, the protocol, efficacy, and mechanism of acupuncture in animal models of vascular dementia are still controversial. Based on the above problems, we initiated this comprehensive study. METHODS: To analyze the literatures included in this study, 4 databases were searched and the SYRCLE’s Risk of bias tool was employed. To perform the subgroup analysis of different acupuncture methods, the Review Manager 5.3 was applied. Meanwhile, the pairwise and network meta-analysis were conducted using Addis 1.16.8. The outcomes included escape latency, number of crossings, time spent in the target quadrant, and swimming speed. RESULTS: Forty-two studies with a total of 1486 animals were included in this meta-analysis. According to the results from subgroup analysis, GV20 + ST36 (Baihui + bilateral Zusanli) combined with 14-day manual acupuncture can obtain best improvement of the rats cognitive function among all acupuncture regimens (MD:-23.41; 95%CI: -26.66, -20.15; I2=0%; P<0.001). The heterogeneity of other acupuncture treatments was significantly higher than that of GV20 + ST36, because the treatment courses were not uniform. Pair-wise and network comparisons are highly consistent. The major results of the network meta-analysis were as follows, In comparison to the impaired group, the acupuncture group showed significantly reduced escape latency (MD:-25.87; 95%CI: -30.75, -21.12), increased number of original platform crossings (MD:2.63; 95%CI: 1.94, 3.34) and time spent in the target quadrant (MD:7.88; 95%CI: 4.25, 11.44). The overall results of the network meta-analysis are as follows: the normal and sham-operated groups performed the best, followed by medicine and acupuncture, while no effect was found in the impaired group treated with non-acupoint and palliative. CONCLUSIONS: Acupuncture significantly improves cognitive function in rats with vascular dementia. Compared to other acupuncture plans, (GV20 + ST36, MA) and 14 -day manual acupuncture can be used to obtain better results. The main mechanism of acupuncture in the treatment of vascular dementia is reduced oxidative stress, neuronal inflammation, and apoptosis, as well as the increased synaptic plasticity and neurotransmitters.